The development of memory in infancy and childhood [ - Courage, Mary; Cowan, Nelson (Studies in developmental psychology, 2009)
The origin of memory in childhood is the focus of vigorous research and debate. Providing a thorough update of topics covered in the first edition, this book also offers new research on significant themes and ideas that have emerged recently